Upgrading New Zealand's competitive advantage: a critique and some proposals - Burnell, Stephen; Sheppard, David (School of Management Working Papers, 1992)
The competitve advantage of nations by M. Porter, and Upgrading New Zealand's competitive advantage by G. Crocombe, M. Enright and M. Porter, both contain a number of fascinating - though often unbacked - propositions concerning the optimal set of rules for an economy. In particular, Upgrading New Zealand's competitive advantage seeks to stimulate debate on those rules that will lift New Zealand out of its current recession and generate sustainable economic growth. Using the New-Classical paradigm, this paper constructs a framework within which these propositions can be rigorously analysed. In addition, a small number of modest proposals are made.